Involvement of circRNA_0007059 in the regulation of postmenopausal osteoporosis by promoting the microRNA‐378/BMP‐2 axis. (25th November 2020) - Liu, Shu; Wang, Chao; Bai, Jinyi; Li, Xiaoming; Yuan, Jiabin; Shi, Zhicai; Mao, Ningfang
Abstract: Increasing evidence suggests that postmenopausal osteoporosis (PMO), a severe disturbance, imposes heavy physical, psychosocial, and financial burdens and dramatically influences the quality of life of postmenopausal women. Circular RNAs (circRNAs) and microRNAs (miRs) play important roles in the occurrence and development of PMO. However, the roles of circRNAs and miRs in osteoporosis regulation still need to be further investigated. circRNAs with different expression levels in patients with PMO were screened via RNA‐seq and bioinformatics analysis. We found that circ_0007059 was upregulated in patients with PMO and during osteoclastogenesis of human bone marrow stromal cells (hBMSCs). Next, we investigated the effect of circ_0007059 overexpression during osteoclastogenesis of hBMSCs. circ_0007059 overexpression attenuated hBMSC differentiation into osteoclasts in vitro. This was demonstrated by downregulated bone morphogenetic protein 2 (BMP‐2) expression, upregulated osteoclast‐specific gene expression, and TRAP staining. circ_0007059 was demonstrated to directly target miR‐378, which in turn targeted BMP‐2 via bioinformatics analysis and the dual‐luciferase reporter assay. Transfection of the miR‐378 mimic reversed the effect of circ_0007059 on the osteoclastogenesis of hBMSCs. These results suggest that circ_0007059 plays an important role in osteoclastogenesis via the miR‐378/BMP‐2 signaling pathway. Targeting the circ_0007059/miR‐378/BMP‐2 axis is possibly a novel idea in osteoporosis treatment.